Developing the assessment literacy of university proficiency test users. (July 2013) - O'Loughlin, Kieran
The rapidly increasing use of English language proficiency test scores by universities around the world to select international students has resulted in a range of admissions, marketing, academic and teaching support staff interacting with the tests in different ways. To date, there has been little research investigating the assessment literacy needs of these test score users. This article focuses on a study into the nature of these needs, how well they are currently being met and how they might be best addressed in the future. Data about these questions in relation to the most widely accepted test in Australian universities, IELTS (International English Language Testing System), were collected from an online survey completed by 50 members of staff who used the test in their work and from follow-up interviews with 15 of these survey respondents. The results indicated that the participants mostly needed information about IELTS for advising prospective students about English language entry requirements and making admissions decisions. They mainly focused on the minimum test scores required for entry and believed their informational needs were reasonably well met by their institution's entry regulations and the IELTS official website. The most popular methods for learning about the IELTS test were information sessions and online tutorials. The results and their implications are discussed in detail.